Comparative study on different strategies for synthesizing all-silica DD3R zeolite crystals with a uniform morphology and size. Issue 46 (23rd July 2020) - Peng, Anna; Lu, Xinqing; Ma, Rui; Fu, Yanghe; Wang, Shuhua; Zhu, Weidong
Abstract : A facile protocol was developed to synthesize pure DD3R crystals with a controllable morphology and size, as well as high reproducibility and productivity. Abstract : In the last three decades, the all-silica deca-dodecasil 3R (DD3R) zeolite has been extensively studied as a significant potential class of porous materials in adsorptive separations. However, the use of most existing synthesis methods is unable to produce pure DD3R crystals with a uniform morphology and size. The present research, is therefore intended to provide a facile protocol to synthesize pure DD3R crystals with a controllable morphology and size and with a high reproducibility and productivity. Special attention was focused on investigating the effects of the type of seeds and the mineralizing reagent on the phase-purity, morphology, and crystal size of the resultant DD3R crystals. Various techniques, such as X-ray diffraction (XRD), scanning electron microscopy (SEM), N2 adsorption–desorption at 77 K, and thermogravimetric analysis (TGA) were then used to characterize the synthesized samples. The results show that by adding a small amount of "amorphous" DD3R or "amorphous" ZSM-58 seeds, the pure DD3R crystals with a uniform morphology and size can be synthesized using 1-adamantanamine (1-ADA) as a structure-directing agent (SDA), KF was used as a mineralizing reagent, and LUDOX AS-30 as a silicon source at 443 K for 1 d. In addition, the pure, large and uniform hexahedron DD3R crystals can be prepared using fumed silica as seeds, although the crystallization time takes a longer period of 3 d. The present work could stimulate fundamental research and industrial applications of the all-silica DD3R zeolite.